Análise do impacto da taxação do serviço de manejo de resíduos sólidos - Silva, Cosmo Hugo da (2024)
The appropriate management of solid waste has become an important issue for society due to the specific increase in waste generation in recent decades, mainly as a result of changes in the population's consumption profile. In Brazil, this issue has gained considerable attention due to recent legislation and innovative public policies in the sector, which generally aim to modernize management and universalize service provision. In 2020, Law No. 14,026 was specifically approved, which updated the legal framework for basic sanitation in Brazil. Among the main changes proposed by the law is the imposition of charging instruments on the part of municipalities for the provision of water management services. solid waste, which is subject to legal decisions if there is non-compliance. The National Water and Sanitation Agency, the body responsible for regulating the sector, explained that the financial sustainability brought by the application of the fee has positive impacts on the quality of services provided and consequently on public health as a whole, through, for example, less negotiation of diseases. . Within this context, the objective of the present study was to verify whether the cities that opted to implement the mechanism between 2010 and 2018 started to present a lower incidence of water-borne illnesses, caused by contact or ingestion of contaminated water. The data were taken from the Brazilian Institute of Geography and Statistics, the National Sanitation Information System and the Information Technology Department of the Unified Health System. The panel data structure, with municipalities deciding to implement charging mechanisms in different periods of time allowed us to use the estimator proposed by Callaway and Sant'Anna (2021). The method is an improvement on the traditional difference-in-differences model and allows us to verify the effect of the treatment in question under different grouping perspectives. The results found did not indicate a statistically significant effect of improving billing on the incidence of the diseases studied. Carefully checking the data, it was observed that municipalities have great difficulty in collecting revenue, with the resources obtained from the implementation of such a mechanism being responsible for only covering a small percentage of total expenses. Another consequence of this fact was clearly observed through the analysis of service quality indicators, where statistically significant results were found for improvement after charging at points that require a low magnitude of resources, such as the installation of selective collection points. Thus, the study concluded that the taxation mechanism in the sector has not been able to achieve its objectives due mainly to implementation problems.